Using Innovating Teaching Circuit On The Developing Some Triple Jump Physical Abilities and Learning Level In Students Aged 16 – 17 Years Old - Talaat, Firas (Journal of Physical Education, 2018)
The importance of the researcher lies in using modern sport equipment in physical education class within a teaching circuit that develops the physical abilities of students as well as learning triple jump. The researcher aimed at identifying the effect of using modern sport equipment on the development of physical abilities and learning triple jump in the subjects. The researcher used the experimental method. The subjects were (28) high school students. Pretests, main experimental followed by the posttests were applied on the subjects. The data was collected and treated using proper statistical operations to conclude that using modern sport equipments developed the experimental group in the artistic performance and some physical abilities in triple jumping.